Motivation factor in performing physical activity among urban area / Muhammad Bakri Mohd Pauzi - Mohd Pauzi, Muhammad Bakri (Faculty Of Sports Science And Recreation, 2019)
Physical activity is well-defined as the body movement at any part that was created by the skeletal muscle of the body which is requires some energy expenses and energy beyond the basal metabolic rate. This study is designed to identify the motivation factor level and variable in performing physical activity and to investigate significant difference motivation factor among gender. The Physical Activity and Leisure Motivation Scale (PALMS) have been used in this study to identify motivation factor level. A total of 150 people (N= 150) from Bandar Utama Selangor that represents urban area were selected through convenience sampling. The result of this study showed that the highest ranking of the motivation factor level was physical condition (M= 4.55, SD= .468) whereas the lowest was Others expectation (M= 2.54, SD= .933). Besides, for the significant difference motivation factor among gender. The result showed, there was 4 factor had significant difference motivation factor between gender which was enjoyment, physical condition, psychological condition, competition/ego. Whereas the others 4 factor had no significant difference between gender which was mastery, appearance, others expectation, affiliation. To conclude, the present study suggests that motivation factors in performing physical activity were different on a gender.